Studi Yuridis Normatif Implementasi Regulasi Perselisihan Hubungan Industrial - Nuryansyah Irawan (Pusat Pengembangan Kebijakan Ketenagakerjaan Kementerian Ketenagakerjaan Republik Indonesia, 2023)
The settlement process of industrial relations disputes in Indonesia includes a bipartite process up to the first court stage trial and cassation by means of prioritizing a fast, precise, fair, and cheap court process; however, in reality, the application could not be fulfilled in Indonesia. This writing aims to describe the renewal of labor law concerning the settlement process of industrial relations in determining labor relations in Indonesia. This study uses the normative juridical method tending to Legal Reform with a Law Renewal approach, which oriented a law theory to understand the aspect of Labor Law according to Indonesian Law. Secondary data was acquired from a library study. Along conclusion statement technique uses the deductive method. The optimum Settlement dispute process can be done with all parties to have the best outcome for all. It is advised to constitutional makers and related instances to accelerate the industrial relation settlement dispute process in order to optimize the result for both sides